2022
DOI: 10.1155/2022/7157507
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A1 Gene Expression and Cellular Copper Levels between Low and Highly Metastatic Osteosarcoma Provide a Case for Novel Repurposing with Disulfiram and Copper

Abstract: Aldehyde dehydrogenase 1A1 (ALDH) is a cancer stem cell marker highly expressed in metastatic cells. Disulfiram (Dis) is an FDA-approved antialcoholism drug that inhibits ALDH and has been studied as a candidate for drug repurposing in multiple neoplasia. Dis cytotoxicity in cancer cells has been shown to be copper-dependent, in part due to Dis’s ability to function as a bivalent metal ion chelator of copper (Cu). The objectives of this research were to test ALDH expression levels and Cu concentrations in sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…ALDH is responsible for metabolizing aldehydes into carboxylic acids which may permit cancer cells to resist the oxidative stress imparted by chemotherapeutic agents 28–31 . We also observed that metastatic human OS tumours have reduced copper concentrations compared with non‐metastatic OS tumours 32 . Conversely, OS patients with metastases displayed increased levels of blood serum copper levels compared with patients who did not develop metastases 32 …”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…ALDH is responsible for metabolizing aldehydes into carboxylic acids which may permit cancer cells to resist the oxidative stress imparted by chemotherapeutic agents 28–31 . We also observed that metastatic human OS tumours have reduced copper concentrations compared with non‐metastatic OS tumours 32 . Conversely, OS patients with metastases displayed increased levels of blood serum copper levels compared with patients who did not develop metastases 32 …”
Section: Introductionmentioning
confidence: 54%
“…Dog tumour, bone, and serum samples were processed and stored as described above. Copper concentrations were determined using a PerkinElmer Analyst 600 atomic absorption spectrophotometer adjusted to detect copper (324.8 nm) as previously described 32,51 . The final copper concentrations were calculated as total μg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations